El desafío de enseñar a enseñar (ciencias jurídicas) sin presencialidad en entornos virtuales - Devetac, Roald (2021)
The essential purpose of this paper is to think about the ways of teaching how to teach law or legal sciences in various virtual learning environments. It has been written taking into consideration not only the experience gathered throughout four years of work at the Department of Teaching Residency from the Secondary and Higher Education Teaching Degree of the University of Buenos Aires Law School, but also the educational decisions and adaptations necessarily adopted during the last three terms in order to meet the governmental and institutional health measures due to the COVID-19 pandemic. Moreover, the work that is being carried out at the DeCyT 2013 (2020-2022) research project within the Research Office of the same academic unit has been likewise taken into account. This presentation consists of three sections: a context and conceptual framework accounting for a theoretical framework that enables us to sift out and analyze the proposed experience, effectively designed and developed; the adjustments and contributions made to the several working procedures of the Department; and, lastly, a conclusion that gathers the strengths based on this experience and that enables us to keep on thinking and, may be, providing some signs to answer the main question of this research: "New education practices: transition or permanence?"